1. The problem statement, all variables and given/known data I am unsure what to do here. I'm given the equation 5(x+1)3 = -5 , and I was given the equation 5(x+1)3 = 0 beforehand. The latter equation has an 'x' value of -1 only, right. However, for the former equation, because I brought the '-5' across the equal sign I realize the roots are not just -1 anymore. 3. The attempt at a solution 5(x+1)3 = -5 5(x+1)(x+1)(x+1)+5 = 0 5x3+15x2+15x+5+5 = 0 5(x3 + 3x2 + 3x + 2) = 0 But after this I'm lost. If I factor: 5x2(x-5)+5(3x+2) = 0 then I have (x-5) which means x = 5, but I'm lost as to where I go next since there should be three roots. (3x+2) gives me x = -2/3. But when I do the 5x2 +5 [should I get this?] I end up with x = sqrt(-1). I don't understand what this is supposed to mean. I figure I must have gone wrong somewhere.